Association between altered tryptophan metabolism, plasma aryl hydrocarbon receptor agonists, and inflammatory Chagas disease - Ambrosio, Laura Fernanda; Volpini, Ximena; Quiroz, Juan Nahuel; Brugo, María Belén; Knubel, Carolina Paola; Herrera, Melisa Rocío; Fozzatti, Laura; Avila Pacheco, Julián; Clish, Clary B.; Takenaka, Maisa C.; Beloscar, Juan; Theumer, Martín Gustavo; et al. (Frontiers in Immunology, 2024)
agonist activation. Additionally, B6 mice exhibited no detectable AhR agonist activity in plasma and displayed lower CYP1A1 up-regulation and AhR expression upon agonist activation. Similarly, CCC patients had decreased AhR agonistic activity in plasma compared to HD patients and exhibited dysregulation in Trp metabolic pathways, resulting in altered plasma metabolite profiles. Notably, patients with severe CCC specifically showed increased N-acetylserotonin levels in their plasma. The methods and findings presented here contribute to a better understanding of CCC development mechanisms and may identify potential specific biomarkers for T. cruzi infection and the severity of associated heart disease. These insights could be valuable in designing new therapeutic strategies. Ultimately, this research aims to establish the AhR agonistic activity and Trp metabolic profile in plasma as an innovative, non-invasive predictor of prognosis for chronic Chagas disease.